Distribution and Growth of Garcinia brasiliensis Mart. and Hevea spruceana (Benth.) müll. arg. in A seasonally flooded forest in Manaus, Amazonas State - Silva Marinho, Tatiana Andreza da; Lopes, Aline; Assis, Rafael Leandro de; Ramos, Santiago Linorio Ferreyra; Gomes, Liene Rocha Picanço; Wittmann, Florian Karl; Schöngart, Jochen (Ciência Florestal, 2013)
This study assessed the distribution and growth of two tree species in a seasonal mixed-water inundation forest near the city of Manaus, and determined the annual growth rates and ages of trees. The aboveground wood biomass was estimated for each population. Eight plots of 25 × 25 m were established, where all individuals of the species Garcinia brasiliensis and Hevea spruceana with heights ≥ 1.0 m were inventoried and mapped. The levels of inundation were measured on all individuals, while the relative photosynthetically active radiation (rPAR) was measured in individuals < 10 cm diameter at breast height (dbh). For eachindividual, the basal area was determined, and the tree volume estimated. Tree ages and the radial increment rate were determined by using dendrochronological methods. In total, 105 individuals were recorded. In both populations, most individuals presented dbh smaller than 10 cm. Hevea spruceana presented more individuals (n = 80), and higher rates of radial increment, while Garcinia brasiliensis (n = 25) presented higher mean age. The duration and height of inundation and the levels of rPAR were different for each population. It was detected significant correlations between dbh and tree heights, and between dbh and tree age. The micro-topographical variations appear to exert effects on the structure population and on the distribution of the studied species. Despite the low rPAR values and variations recorded within the study site, the different light requirements in each species suggest different ecological niches.
Distribuição e crescimento de garcinia brasiliensis mart. e hevea spruceana (benth.) müll.arg. em uma floresta inundável em manaus, Amazonas
Keywords: Garcinia; Hevea; Hevea Spruceana